The Role of service quality, product quality, location and product innovation on consumer purchasing decisions and word of mouth - Praditya, Rayyan Aqila (Journal of Industrial Engineering & Management Research, 2024)
This research aims to determine the influence of product quality, service quality, location and product innovation on purchasing decisions using word of mouth. The subjects of this survey were 450 visitors. Validity and reliability tests are used to measure the validity and reliability of research tools in the form of questionnaires. Hypothesis Test analysis has been carried out using SmartPLS. In this research, researchers used Outer Model Testing and Inner Model Testing. The results of the research show that product quality has a positive and significant effect on purchasing decisions, service quality has a positive and significant effect on purchasing decisions, location has a positive and significant effect on purchasing decisions, product innovation has a positive and significant effect on purchasing decisions. purchasing decisions have a significant positive effect, word of mouth as a moderating variable weakens the influence of product quality on purchasing decisions, word of mouth as a moderating variable strengthens the influence of service quality on purchasing decisions, word of mouth as a moderating variable weakens the influence of location on purchasing decisions, and word of mouth as a moderating variable weakens the influence of product innovation on purchasing decisions.